DIFFERENTIAL EFFECTIVENESS OF MONTESSORI DIDACTIC AND DIRECT INSTRUCTIONAL METHODS ON REASONING ABILITY OF CHILDREN WITH HEARING IMPAIRMENT IN LAGOS, NIGERIA - Adeniyi, Samuel Olufemi; Kuku, OlaotanOladele (Specijalna edukacija i rehabilitacija, 2018)
Language has a noteworthy role in the cognitive development and social ability of an individual. However, a delay in language could affect an individual ability to think critically. This could be breached through impactful method of instruction from elementary school. Thus, this study examined the differential effectiveness of Montessori didactic and Direct Instructional methods on reasoning ability of children with hearing impairment in Lagos State. The research design was a quasi-experimental pretest, posttest control group. All children with hearing impairment in Lagos State constituted the population of the study while the sample size was 29 pupils comprising 15 male and 14 female pupils with hearing impairment. The simple random, hat and draw method and purposive sampling were used in the selection of the sample. Two research hypotheses were tested at 0.05 level of significance. The Reasoning Ability Test was used to gather relevant data while mean, standard deviation, mean difference, Analysis of Covariance (ANCOVA) and Least Significant Difference (LSD) were the statistical tool used to analyse the data. The study found out that both Montessori Didactic Material and Direct Instruction group were efficacious in teaching pupils with hearing impairment. However, the former was be more effective. Besides, the teaching methods do not have significant gender effect on pupils with hearing impairment. It was recommended that montessori didactic method should be employed in teaching of elementary school pupils because it encourages active participation in learning process in form of self- directional and independence not minding gender, intellectual and economic disparities.